1999
DOI: 10.1016/s0014-5793(99)00935-7
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐dependent degradation of SulA, a cell division inhibitor, by the HslVU protease in Escherichia coli

Abstract: HslVU is an ATP-dependent protease consisting of two multimeric components, the HslU ATPase and the HslV peptidase. To gain an insight into the role of HslVU in regulation of cell division, the reconstituted enzyme was incubated with SulA, an inhibitor of cell division in Escherichia coli, or its fusion protein with maltose binding protein (MBP). HslVU degraded both proteins upon incubation with ATP but not with its nonhydrolyzable analog, ATPQ QS, indicating that the degradation of SulA requires ATP hydrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 40 publications
4
74
0
Order By: Relevance
“…In the presence of the nonhydrolyzable ATP-␥S, wild-type HslVU degrades the chromogenic peptide and casein, but not MBP-SulA (18). On the basis of these results, it has been suggested that only ATP binding but not its hydrolysis is a prerequisite for peptidase and caseinolytic activities, whereas ATP binding and hydrolysis are necessary for MBP-SulA degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of the nonhydrolyzable ATP-␥S, wild-type HslVU degrades the chromogenic peptide and casein, but not MBP-SulA (18). On the basis of these results, it has been suggested that only ATP binding but not its hydrolysis is a prerequisite for peptidase and caseinolytic activities, whereas ATP binding and hydrolysis are necessary for MBP-SulA degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The activity assay was conducted at 37°C using storage buffer containing 7.5% (v/v) dimethylformamide in a total volume of 200 l, and the release of AMC was monitored as a fluorescence increment at 440 nm (excited at 360 nm) by using a SpectraMax M5 system (Molecular Devices, Inc.) with a 96-well plate (Corning). For protein substrate degradation, the MBP-SulA was used as described previously (20,31,35).…”
Section: Methodsmentioning
confidence: 99%
“…There are two potential HslU molecules, HslU1 and HslU2, in T. brucei (TbHslU1 and TbHslU2) that have high identity with the HslU from E. coli (EcHslU; Fig. 1B) (28 In order to understand the molecular features of the eukaryotic HslVU system, we performed biochemical characterization of TbHslV and TbHslU by using a synthetic substrate, benzyloxycarbonyl-Gly-Gly-Leu-7-amido-4-methyl coumarin (Z-GGL-AMC) (4,30) and a natural substrate of EcHslU, the SulA protein (31,32). Although both TbHslU1 and TbHslU2 regulate mitochondrial DNA replication (28), we found that only TbHslU2 acts as an activator of TbHslV protease.…”
mentioning
confidence: 99%
“…6C). We have previously shown that ATP␥S, a non-hydrolysable ATP analog, increases the interaction between HslV and HslU and thereby supports the peptide hydrolysis by the HslVU complex much better than ATP (18). Thus, it appears likely that the increased peptidase activity of mixed dodecamers containing up to 5-6 T1⌬ subunits is due to the T1⌬-mediated increase in the interaction between HslV and HslU despite the fact that T1⌬ subunits in the dodecamers are catalytically inactive.…”
Section: Effect Of Increasing Numbers Of T1⌬ Subunits In An Hslv Dodementioning
confidence: 99%
“…Moreover, HslV that by itself is a weak peptidase can be activated 1-2 orders of magnitude by ATP-bound HslU (15,16). ATP␥S, 4 a nonhydrolyzable ATP analog, also supports HslV-mediated hydrolysis of small peptides but not that of native protein substrates, such as SulA, suggesting the role of ATP hydrolysis by HslU in unfolding of protein substrates for their access to and subsequent degradation at the inner proteolytic chamber of dodecameric HslV (18). Importantly, chemical cross-linking analysis has shown that ATP-bound HslU interacts with HslV to form the HslVU complex, but ADP-bound HslU does not, implicating dynamic interaction between HslU and HslV during ATP hydrolysis cycles (17).…”
mentioning
confidence: 99%